مركز البحث في الأنثروبولوجيا وهران رهان تحدي - نقادي, سميرة (Changement Social, 2018)
ان المركز الوطني للبحث في الأنثروبولوجيا الاجتماعية والثقافية بوهرانCRASCأحد أهم مراكز الاشعاع العلمي والبحث الأكاديمي انطلاقا من اصداراته كمجلة انسانيات الدولية والمجلة الافريقية للكتاب ودفاتر الكراسك وبريد الكراسك الى جانب منشورات يساهم فيها باحثين دائمين وباحثين مشاركين يرفعون رهان التحدي ليكون المركز طليعة المراكز الأنثروبولوجيا خاصة والعلوم الاجتماعية عامة. ان المركز ذو الفروع المتعددة مثل فرع الرصيد بالجزائر العاصمة ومركز البحث بقسنطينة يعمد على تغطية الأنثروبولوجيا التاريخية والاجتماعية الى جانب الطوبونيميا المهتمة بأسماء الأماكن في حين تتنوع وحدات البحث الخاصة بوهران الى ستة وحدات وهي : وحدة  أنثروبولوجيا التاريخ والذاكرة ووحدة مدن وأقاليم وحدة المخيالوالسيرورات ووحدة أنثروبولوجيا التربية وأنظمة التكوين،الى جانب وحدة البحث حول الترجمة والمصطلحات ووحدة الثقافة والاتصال والفنون. The National Research Center in Social and Cultural Anthropology is one of the most important academic research centers. The center is best known for its scientific publications: the Insaniyat journal, the Africa review of books, les cahiers du crasc… The CRASC is divided to many units, the one located in Algiers is interested in toponomy (RASYD), the Constantine unit is covering the historical and social anthropology studies. Plus another one placed in Oran, specialized on translation and terminology.     The center itself is subdivided into five divisions: the historical anthropology and memory unit, Cities and Regions unit, Imagination and Processes unit and Education Anthropology and  formation systems. These divisions work to promote research by publishing books and reports, in order to  strengthen the public policies to serve the society, the state, science and knowledge. The main question of this paper is: What place has anthropology in this center? In other words how the anthropological academic research are made in this center ? To answer these questions, we have reviewed the history of the center, the beginning, progress and the current state, by covering the Insaniyat journal and ARB review.